Synthetic resin composition, fireproof material, sealant, adhesive and joint structure

JP7641051B2Active Publication Date: 2025-03-06SEKISUI FULLER CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024006538
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-05-08
Filing Date
2024-01-19
Publication Date
2025-03-06
Estimated Expiration
2039-05-08

AI Technical Summary

Benefits of technology

【0129】 本発明の合成樹脂組成物は、燃焼により生成された燃焼残渣が非常に強固であり、この燃焼残渣は、火災時においても目地部を充填し閉塞した状態を確実に保持して目地部などのシーリング部からの炎の回り込みを阻止し、建築構造物の壁部などに優れた耐火性能を付与することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641051000001
    Figure 0007641051000001
  • Figure 0007641051000002
    Figure 0007641051000002
  • Figure 0007641051000003
    Figure 0007641051000003
Patent Text Reader

Abstract

To provide a synthetic resin composition in which a combustion residue generated by combustion is strong.SOLUTION: A synthetic resin composition has strength of a combustion residue after having been combusted under an atmosphere of 800°C for 20 minutes of 0.5 N / mm2, and accordingly the combustion residue generated by combustion is extremely strong. The combustion residue surely holds a state where a joint part is filled and closed in the case of fire, prevents wraparound of flame from a sealing part such as a joint part, and can impart excellent fire-resistant performance to a wall part of a construction structure.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a synthetic resin composition, a fire-resistant material, a sealant, an adhesive, and a joint structure. [Background technology]

[0002] The joint structure of an architectural structure is formed by filling joints formed between wall members constituting a wall with a sealant.

[0003] In the above-mentioned joint structure, since the sealant is an organic substance, it is vulnerable to combustion, and in the event of a fire, the sealant may fall off from the joint, allowing flames to seep in through the joint, resulting in the problem that the fire resistance of the walls of the building structure is insufficient.

[0004] Patent Document 1 discloses a fireproof sealant comprising (A) a polyalkylene ether having a silicon-containing functional group at its end that can form a silanol group by hydrolysis, (B) a microencapsulated ammonium polyphosphate powder, (C) a calcium carbonate powder, and (D) a silanol condensation catalyst. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 3848379 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the above-mentioned fireproof sealant foams due to the heat during a fire and then forms a charred layer film. However, the foaming makes the combustion residue brittle, so it is easily destroyed by the wind pressure of the combustion flame and falls off from the joints, resulting in the problem that the fire resistance of the walls of building structures is still insufficient.

[0007] The present invention provides a synthetic resin composition which produces strong combustion residues upon combustion.The present invention provides a synthetic resin composition which can be suitably used as a fire-resistant material, a sealant, and an adhesive.The present invention provides a sealant which reliably maintains its state of being filled into sealed parts such as joints even in the event of a fire, prevents flames from penetrating through the sealed parts, and can impart excellent fire resistance to the walls of architectural structures. [Means for solving the problem]

[0008] The synthetic resin composition of the present invention contains a synthetic resin, and after burning for 20 minutes in an atmosphere of 800°C, the strength of the combustion residue is 0.5 N / mm 2 The present invention is characterized in that:

[0009] The strength of the combustion residue of the synthetic resin composition is 0.5N / mm 2 Above 1.0N / mm 2 More than 2.0N / mm is preferable. 2 More preferably, 5.0N / mm 2 More preferably, 10N / mm 2 The strength of the combustion residue of the synthetic resin composition is more preferably 20 N / mm 2 The strength of the combustion residue is preferably 0.5 N / mm 2 If the composition is more than this, it is possible to prevent the combustion residue of the synthetic resin composition or its cured product (hereinafter, "synthetic resin composition or its cured product" may be collectively referred to as "solid material") from being destroyed by wind pressure, etc. Furthermore, even in the event of a fire, the composition will not fall off from sealing parts such as joints, and the sealing parts will remain filled, thereby maintaining the fire resistance of the walls of architectural structures. Furthermore, decorative items such as tiles attached to the surface of a wall using the synthetic resin composition can be stably maintained in a state of being attached to the wall surface even in the event of a fire. The strength of the combustion residue is 20 N / mm 2When the content is less than 100%, the flexibility of the solid matter of the synthetic resin composition is improved. In addition, the filling state of the sealing part can be reliably maintained by following the expansion of the sealing part, and the fire resistance of the wall part of the architectural structure can be maintained. Decorative articles such as tiles attached to the wall surface using the synthetic resin composition can be stably maintained in the state of being attached to the wall surface even in the event of a fire.

[0010] In a synthetic resin composition, the strength of the combustion residue after burning for 20 minutes in an atmosphere of 800°C refers to a value measured in the following manner.

[0011] The synthetic resin composition is molten and then applied to a zinc ore plate to a thickness of 10 mm, width of 10 mm and length of 50 mm. The synthetic resin composition is then cured for one month in an environment of 23°C and relative humidity of 50% to harden or solidify the synthetic resin composition, thereby obtaining a test specimen.

[0012] The test specimen is left in a thermostatic chamber at 800°C for 20 minutes to be burned, then removed from the chamber and left in an atmosphere at 23°C and a relative humidity of 50% for 3 hours to generate combustion residue.

[0013] The coating strength of the combustion residue is measured by compressing the combustion residue with a needle having a diameter of 1.5 mm at a compression speed of 50 mm / min using a universal testing machine, and the coating strength is regarded as the strength of the combustion residue.

[0014] The synthetic resin composition has a 50% modulus of 0.05 to 0.40 N / mm after curing an I-type test specimen in accordance with the standard JTC S-0001 of the NPO Housing Exterior Wall Technical Center at 23°C and a relative humidity of 50% for 28 days. 2 It is preferable that the 50% modulus is within the above range. When the synthetic resin composition has excellent flexibility, it smoothly follows the variation of the gap dimension of the sealing part and reliably maintains the state where it is filled in the sealing part. Furthermore, decorative items such as tiles attached to the wall surface using the synthetic resin composition can be stably maintained in the state where they are attached to the wall surface even in the event of a fire.

[0015] The synthetic resin composition preferably has an elongation rate of 400% or more after curing an I-type test specimen conforming to the standard JTC S-0001 of the NPO Housing Exterior Wall Technical Center at 23°C and a relative humidity of 50% for 28 days. The solid matter of the synthetic resin composition has excellent flexibility. The dimensions of sealing parts such as joints formed between wall members constituting a wall change due to vibrations caused by earthquakes and expansion and contraction of the wall members due to temperature changes. When the elongation rate of the synthetic resin composition is 400% or more, the solid matter of the synthetic resin composition smoothly follows the dimensional changes of the sealing parts without breaking, and can maintain the closed state of the joints to exhibit excellent waterproofing. Furthermore, decorative items such as tiles attached to the wall surface using the synthetic resin composition can be stably maintained in the state attached to the wall surface even in the event of a fire.

[0016] The 50% modulus and elongation percentage of an I-type specimen conforming to the NPO Housing Exterior Wall Technical Center standard JTC S-0001 after curing for 28 days at 23°C are values ​​measured as follows. An I-type specimen conforming to the NPO Housing Exterior Wall Technical Center standard JTC S-0001 is prepared using a synthetic resin composition. The obtained I-type specimen is cured for 28 days at 23°C and 50% relative humidity, and cured as necessary to prepare a specimen. The 50% modulus and elongation percentage of the specimen are measured in accordance with the NPO Housing Exterior Wall Technical Center standard JTC S-0001.

[0017] The synthetic resin composition can be suitably used as an adhesive, as described below. The shear strength of the adhesive is 1.0 N / mm 2 The adhesive shear strength is preferably 1.0N / mm 2 When the adhesive has a shear strength of 100% or more, the adhesiveness of the adhesive is improved. The shear strength of the adhesive is a value measured in accordance with JIS K6850.

[0018] The synthetic resin composition had a strength of 0.5 N / mm after burning for 20 minutes in an 800°C atmosphere. 2The synthetic resin composition is not particularly limited, but preferably contains a synthetic resin, a mineral having a Mohs hardness of 5 or more, and a binder component.

[0019] Hereinafter, a synthetic resin composition containing a synthetic resin, a mineral having a Mohs hardness of 5 or more, and a binder component will be described.

[0020] [Synthetic resin] The synthetic resin is not particularly limited. The synthetic resin may be either a non-curable resin or a curable resin, but a curable resin is preferred. The non-curable resin has a viscosity of 23° C. and 1.01×10 5 The curable resin is preferably a solid at 23° C. and 1.01×10 Pa (1 atmosphere) after curing. 5 It is preferably a solid at 1 atm.

[0021] The number average molecular weight of the non-curable resin is preferably more than 10,000, and more preferably 10,100 or more. The number average molecular weight of the synthetic resin is preferably 1,000,000 or less. The number average molecular weight of the one-component curable resin is preferably more than 10,000, and more preferably 10,100 or more. The number average molecular weight of the synthetic resin is preferably 1,000,000 or less. The number average molecular weight of the synthetic resin refers to a value measured in the same manner as the method for measuring the number average molecular weight of a polyalkylene oxide having a hydrolyzable silyl group described later.

[0022] Examples of non-curable resins include rubber-based polymers and polyolefin-based polymers (eg, polyethylene-based resins, polypropylene-based resins, etc.).

[0023] Examples of rubber polymers include ethylene-propylene rubber (EPM), natural rubber, isoprene rubber, butadiene rubber, butyl rubber, styrene-butadiene rubber, styrene-isoprene rubber, styrene-isoprene-butadiene rubber, acrylonitrile-butadiene rubber, and ethylene-vinyl acetate copolymer.

[0024] The curable resin includes a one-component curable resin and a two-component curable resin.

[0025] [1-component curable resin] Examples of the one-component curable resin include a polymer having a hydrolyzable silyl group and a polymer having a hydrolyzable isocyanate group, and it is preferable to include a polymer having a hydrolyzable silyl group. In the polymer containing a hydrolyzable silyl group, the hydrolyzable group of the hydrolyzable silyl group is hydrolyzed in the presence of water to generate a silanol group (-SiOH). Then, the silanol groups are dehydrated and condensed to form a crosslinked structure. In the polymer having a hydrolyzable isocyanate group, the hydrolyzable isocyanate group generates a urea bond (-NHCONH-) while generating carbon dioxide in the presence of water to form a crosslinked structure.

[0026] The hydrolyzable silyl group is a group in which 1 to 3 hydrolyzable groups are bonded to a silicon atom. The hydrolyzable group of the hydrolyzable silyl group is not particularly limited, and examples thereof include a hydrogen atom, a halogen atom, an alkoxy group, an acyloxy group, a ketoximate group, an amino group, an amide group, an acid amide group, an aminooxy group, a mercapto group, an alkenyloxy group, and an oxime group.

[0027] Among them, the hydrolyzable silyl group is preferably an alkoxysilyl group because the hydrolysis reaction is mild. Examples of the alkoxysilyl group include trialkoxysilyl groups such as trimethoxysilyl group, triethoxysilyl group, triisopropoxysilyl group, and triphenoxysilyl group; dialkoxysilyl groups such as propyldimethoxysilyl group, methyldimethoxysilyl group, and methyldiethoxysilyl group; and monoalkoxysilyl groups such as dimethylmethoxysilyl group and dimethylethoxysilyl group.

[0028] The hydrolyzable isocyanate group refers to an isocyanate group that can form a urea bond (-NHCONH-) by hydrolysis.

[0029] [Polymers having hydrolyzable silyl groups] The polymer having a hydrolyzable silyl group is not particularly limited, and examples thereof include polyalkylene oxide having a hydrolyzable silyl group, acrylic polymer having a hydrolyzable silyl group, silicone resin having a hydrolyzable silyl group, urethane resin having a hydrolyzable silyl group, polyolefin resin having a hydrolyzable silyl group, etc. The polymer having a hydrolyzable silyl group preferably contains a polyalkylene oxide having a hydrolyzable silyl group, and more preferably contains a polyalkylene oxide having a hydrolyzable silyl group and an acrylic polymer having a hydrolyzable silyl group. The polymer having a hydrolyzable silyl group may be used alone or in combination of two or more kinds.

[0030] [Polyalkylene oxide having hydrolyzable silyl groups] The hydrolyzable silyl group contained in the polyalkylene oxide having a hydrolyzable silyl group is preferably an alkoxysilyl group, more preferably a dialkoxysilyl group, more preferably a dimethoxysilyl group, and particularly preferably a propyldimethoxysilyl group.

[0031] The polyalkylene oxide having a hydrolyzable silyl group preferably has 1 to 4 hydrolyzable silyl groups on average in one molecule. When the number of hydrolyzable silyl groups in the polyalkylene oxide having a hydrolyzable silyl group is within the above range, the combustion residue of the solid matter of the synthetic resin composition can be stably held. For example, the combustion residue of the solid matter of the synthetic resin composition can be stably held in a sealing part such as a joint part, and the fire resistance of the wall part of the building structure can be maintained. The polyalkylene oxide having a hydrolyzable silyl group preferably has a hydrolyzable silyl group at least one of both ends of its main chain.

[0032] In addition, the average number of hydrolyzable silyl groups per molecule in the polyalkylene oxide having hydrolyzable silyl groups is 1It can be calculated based on the concentration of hydrolyzable silyl groups in the polyalkylene oxide determined by H-NMR and the number average molecular weight of the polyalkylene oxide determined by GPC.

[0033] The polyalkylene oxide constituting the polyalkylene oxide having a hydrolyzable silyl group has a main chain represented by the general formula: -(RO) n - (wherein R represents an alkylene group having 1 to 14 carbon atoms, and n represents the number of repeating units and is a positive integer) is preferred. The main chain skeleton of the polyalkylene oxide may be composed of only one type of repeating unit, or may be composed of two or more types of repeating units.

[0034] Examples of the main chain skeleton of the polyalkylene oxide include polyethylene oxide, polypropylene oxide, polybutylene oxide, polytetramethylene oxide, polyethylene oxide-polypropylene oxide copolymer, and polypropylene oxide-polybutylene oxide copolymer. Among them, polypropylene oxide is preferable. Polypropylene oxide can impart excellent rubber elasticity and adhesiveness to the solid of the synthetic resin composition.

[0035] The number average molecular weight of the polyalkylene oxide having a hydrolyzable silyl group is preferably 3000 to 50000, more preferably 10000 to 30000. When the number average molecular weight of the polyalkylene oxide is 3000 or more, the mechanical strength or elongation of the solid of the synthetic resin composition is improved. When the number average molecular weight of the polyalkylene oxide is 50000 or less, the coatability of the synthetic resin composition is improved.

[0036] In the present invention, the number average molecular weight of the polyalkylene oxide having a hydrolyzable silyl group means a value calculated in terms of polystyrene measured by GPC (gel permeation chromatography). In the measurement by GPC, for example, Shodex KF800D manufactured by Tosoh Corporation can be used as a GPC column, and chloroform or the like can be used as a solvent.

[0037] The polyalkylene oxide having a hydrolyzable silyl group may be a commercially available product. For example, the polyalkylene oxide having a hydrolyzable silyl group may be a product manufactured by Kaneka Corporation under the trade names "MS Polymer S-203", "MS Polymer S-303", "Silyl Polymer SAT-200", "Silyl Polymer SAT-350" and "Silyl Polymer SAT-400". The polyalkylene oxide having a hydrolyzable silyl group may be a product manufactured by Asahi Glass Company under the trade names "Exestar ESS-3620", "Exestar ESS-2420", "Exestar ESS2410" and "Exestar ESS3430".

[0038] A polyalkylene oxide having a polypropylene oxide main chain and a (methoxymethyl)dimethoxysilyl group at the end of the polypropylene oxide is commercially available from Kaneka Corporation under the product name "HS-2."

[0039] A polyalkylene oxide having a polypropylene oxide main chain and an isopropyldimethoxymethylsilyl group at the end of the polypropylene oxide is commercially available from Kaneka Corporation under the product name "SAX720."

[0040] [Acrylic polymer having hydrolyzable silyl group] As the hydrolyzable silyl group contained in the acrylic polymer having a hydrolyzable silyl group, an alkoxysilyl group is preferable, a trialkoxysilyl group is more preferable, and a trimethoxysilyl group is particularly preferable, because the hydrolysis reaction is mild.

[0041] The acrylic polymer having a hydrolyzable silyl group preferably has 1 to 2 hydrolyzable silyl groups on average in one molecule. The acrylic polymer having a hydrolyzable silyl group more preferably has 1 to 1.8 hydrolyzable silyl groups on average in one molecule. When the number of hydrolyzable silyl groups is 1 or more, the curability of the synthetic resin composition is improved. When the number of hydrolyzable silyl groups is 1.8 or less, the mechanical strength or elongation of the solid matter of the synthetic resin composition is improved. The acrylic polymer having a hydrolyzable silyl group preferably has a hydrolyzable silyl group at least on one of both ends of the main chain.

[0042] The acrylic polymer having a hydrolyzable silyl group may be used in combination with an acrylic polymer not having a hydrolyzable silyl group. In this case, the number of hydrolyzable silyl groups per molecule in the total of both is preferably 0.3 or more, more preferably 0.5 or more. When the number of hydrolyzable silyl groups is 0.3 or more, the curing property of the synthetic resin composition is improved. On the other hand, the number of hydrolyzable silyl groups per molecule in the total of both is preferably 2.0 or less, more preferably 1.8 or less. When the number of hydrolyzable silyl groups is 2.0 or less, the mechanical strength or elongation of the solid of the synthetic resin composition is improved.

[0043] The method for introducing a hydrolyzable silyl group into an acrylic polymer is not particularly limited, and examples thereof include a method in which an unsaturated group is introduced into a copolymer of monomers constituting the main chain skeleton, and then a hydrosilane having a hydrolyzable silyl group is allowed to act on the copolymer to carry out hydrosilylation.

[0044] In addition, the average number of hydrolyzable silyl groups per molecule in the acrylic polymer having hydrolyzable silyl groups is 1 It is calculated based on the concentration of hydrolyzable silyl groups in the acrylic polymer having a hydrolyzable silyl group determined by H-NMR and the number average molecular weight of the acrylic polymer having a hydrolyzable silyl group determined by GPC.

[0045] The main chain skeleton of the acrylic polymer having a hydrolyzable silyl group is preferably a copolymer of a monomer containing methyl (meth)acrylate and butyl (meth)acrylate, more preferably a copolymer of a monomer containing methyl methacrylate and butyl acrylate, and particularly preferably a copolymer of a monomer containing methyl methacrylate and n-butyl acrylate. The acrylic polymer having a hydrolyzable silyl group, the main chain skeleton of which is the copolymer, is preferable because it improves the weather resistance of the synthetic resin composition. Here, (meth)acrylate means methacrylate and / or acrylate.

[0046] In the acrylic polymer having a hydrolyzable silyl group, the content of the methyl (meth)acrylate component is preferably 3 to 70 mass%, more preferably 5 to 50 mass%. When the content of the methyl (meth)acrylate component is 3 mass% or more, the adhesiveness of the synthetic resin composition is improved. When the content of the methyl (meth)acrylate component is 70 mass% or less, the flexibility of the solid matter of the synthetic resin composition is improved.

[0047] In the acrylic polymer having a hydrolyzable silyl group, the content of the butyl (meth)acrylate component is preferably 30 to 97 mass%, more preferably 50 to 95 mass%. By having the content of the butyl (meth)acrylate component be 30 mass% or more, the solid matter of the synthetic resin composition becomes flexible and can follow the sealing parts such as joints, which is preferable.

[0048] In the acrylic polymer having a hydrolyzable silyl group, the monomers used in the polymer constituting the main chain skeleton may further include other monomers in addition to methyl acrylate, methyl methacrylate, butyl acrylate, and butyl methacrylate.Examples of other monomers include styrene derivatives such as styrene, indene, α-methylstyrene, p-methylstyrene, p-chlorostyrene, p-chloromethylstyrene, p-methoxystyrene, p-tert-butoxystyrene, and divinylbenzene; compounds having a vinyl ester group such as vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl benzoate, and vinyl cinnamate; maleic anhydride, N-vinylpyrrolidone, N-vinylmorpholine, methacrylonitrile, acrylonitrile, acrylamide, methacrylamide, N-cyclohexylmaleimide, N-phenylmaleimide, N-laurylmaleimide, N-benzylmaleimide, n-propyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, tert-butyl vinyl ether, tert-amyl vinyl ether, cyclohexyl vinyl ether, 2-ethylhexyl vinyl ether, dodecyl vinyl ether, octadecyl vinyl ether, 2-chloroethyl vinyl ether, ethylene glycol butyl vinyl ether, trimethylsilyl ...butyl vinyl ether, tert-amyl vinyl ether, tert-butyl vinyl ether, tert-butyl vinyl ether, tert-butyl vinyl ether, tert-butyl vinyl ether, tert-butyl vinyl ether, tert-butyl vinyl ether, tert-butyl vinyl ether, tert-butyl vinyl ether, tert-butyl vinyl ether, tert-butyl vinyl ether, tert-butyl vinyl ether, tert-butyl vinyl ether, tert-butyl vinyl ether, tert Examples of the vinyloxy group-containing compounds include ethylene glycol methyl vinyl ether, (4-vinyloxy)butyl benzoate, ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, tetraethylene glycol divinyl ether, butane-1,4-diol-divinyl ether, hexane-1,6-diol-divinyl ether, cyclohexane-1,4-dimethanol-divinyl ether, di(4-vinyloxy)butyl isophthalate, di(4-vinyloxy)butyl glutarate, di(4-vinyloxy)butyl succinate, trimethylolpropane trivinyl ether, 2-hydroxyethyl vinyl ether, 4-hydroxybutyl vinyl ether, 6-hydroxyhexyl vinyl ether, cyclohexane-1,4-dimethanol monovinyl ether, diethylene glycol monovinyl ether, 3-aminopropyl vinyl ether, 2-(N,N-diethylamino)ethyl vinyl ether, urethane vinyl ether, and polyester vinyl ether. These monomers may be used alone or in combination of two or more.

[0049] The polymerization method for the acrylic polymer having a hydrolyzable silyl group is not particularly limited, and any known method can be used. Examples of the polymerization methods include free radical polymerization, anionic polymerization, cationic polymerization, UV radical polymerization, living anionic polymerization, living cationic polymerization, and living radical polymerization.

[0050] The weight average molecular weight of the acrylic polymer having a hydrolyzable silyl group is preferably 1000 to 50000, more preferably 2000 to 30000, and particularly preferably 3000 to 15000. The acrylic polymer having a hydrolyzable silyl group, whose weight average molecular weight is within the above range, improves the flexibility and extensibility of the solid material of the synthetic resin composition.

[0051] [Silicone resin having hydrolyzable silyl groups] Silicone resin refers to a polymer having a main chain formed by repeating siloxane bonds (Si-O-Si). The silicone resin having hydrolyzable silyl groups has a plurality of hydrolyzable silyl groups in the main chain of the silicone resin. The silicone resin having hydrolyzable silyl groups preferably has hydrolyzable silyl groups at both ends of the main chain of the silicone resin. The hydrolyzable silyl group contained in the silicone resin having hydrolyzable silyl groups is preferably an oximesilyl group, more preferably a ketoximesilyl group.

[0052] [Urethane resin having hydrolyzable silyl group] The urethane resin refers to a polymer having a main chain formed by repeating urethane bonds (-NHCOO-). The urethane resin having a hydrolyzable silyl group has a plurality of hydrolyzable silyl groups in the main chain of the urethane resin. The urethane resin having a hydrolyzable silyl group preferably has hydrolyzable silyl groups at both ends of the main chain of the urethane resin.

[0053] [Polyolefin resins having hydrolyzable silyl groups] Examples of polyolefin resins include polyethylene resins and polypropylene resins. The polyolefin resins having hydrolyzable silyl groups have a plurality of hydrolyzable silyl groups in the main chain of the polyolefin resin. The polyolefin resins having hydrolyzable silyl groups preferably have hydrolyzable silyl groups at both ends of the main chain of the polyolefin resin.

[0054] [Polymer having hydrolyzable isocyanate group] Examples of polymers having hydrolyzable isocyanate groups include urethane resins having hydrolyzable isocyanate groups. Urethane resins refer to polymers having a main chain formed by repeated formation of urethane bonds (-NHCOO-). Urethane resins having hydrolyzable isocyanate groups have a plurality of hydrolyzable isocyanate groups in the main chain of the urethane resin. It is preferable that the urethane resins having hydrolyzable isocyanate groups have hydrolyzable isocyanate groups at both ends of the main chain of the urethane resin. The urethane resins include polyether-based urethane resins made from polyether polyols and polyester-based urethane resins made from polyester polyols, but any of these may be used.

[0055] [2-component curable resin] The two-component curable resin is not particularly limited, and examples thereof include isocyanate-based polymers and glycidyl-based polymers.

[0056] The isocyanate-based polymer is a two-part curable resin consisting of a base agent containing polyisocyanate and a curing agent containing polyol. The base agent and the curing agent are mixed together, and the polyisocyanate and the polyol are reacted to form urethane bonds, which crosslink and cure.

[0057] Examples of polyisocyanates include araliphatic diisocyanates, aliphatic diisocyanates, alicyclic diisocyanates, etc. Examples of araliphatic diisocyanates include diphenylmethane diisocyanate, 1,3-xylylene diisocyanate, 1,4-xylylene diisocyanate, 1,3-bis(1-isocyanato-1-methylethyl)benzene, 1,4-bis(1-isocyanato-1-methylethyl)benzene, ω,ω′-diisocyanato-1,4-diethylbenzene, and urethane prepolymers having isocyanate groups at both ends.

[0058] Examples of the aliphatic diisocyanate include hexamethylene diisocyanate, tetramethylene diisocyanate, 2-methyl-pentane-1,5-diisocyanate, 3-methyl-pentane-1,5-diisocyanate, lysine diisocyanate, and trioxyethylene diisocyanate.

[0059] Examples of alicyclic diisocyanates include isophorone diisocyanate, cyclohexyl diisocyanate, hydrogenated diphenylmethane diisocyanate, norbornane diisocyanate, hydrogenated tolylene diisocyanate, hydrogenated xylene diisocyanate, and hydrogenated tetramethylxylene diisocyanate.

[0060] Examples of the polyol include polyurethane polyol, polyester polyol, polyether polyol, acrylic polyol, polyolefin polyol, and castor oil polyol.

[0061] The glycidyl polymer is a two-liquid curable resin consisting of a main agent containing an epoxy resin and a curing agent. The epoxy resin is not particularly limited, and examples thereof include bisphenol A type epoxy resin obtained by reacting bisphenol A with epichlorohydrin, bisphenol F type epoxy resin obtained by reacting bisphenol F with epichlorohydrin, and hydrogenated products thereof, glycidyl ester type epoxy resin, novolac type epoxy resin, urethane modified epoxy resin, nitrogen-containing epoxy resin such as triglycidyl isocyanurate, and rubber modified epoxy resin containing polybutadiene or NBR.

[0062] The curing agent is not particularly limited, and examples thereof include amine-based curing agents, acid anhydride-based curing agents, polyamide-based curing agents, imidazole-based curing agents, and polymercapran-based curing agents.

[0063] Examples of the amine-based curing agent include aliphatic polyamines such as polyoxypropylenetriamine, diethylenetriamine, and triethylenetetramine, and aromatic polyamines such as metaphenylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, and 2,4,6-tris(dimethylaminomethyl)phenol.

[0064] Examples of the acid anhydride curing agent include tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylnadic anhydride, pyromellitic anhydride, HET anhydride, dodecenyl succinic anhydride, etc. Examples of the polyamide curing agent include dimer acid, etc.

[0065] The synthetic resin preferably contains a polymer having a hydrolyzable silyl group and a glycidyl-based polymer, more preferably a polyalkylene oxide having a hydrolyzable silyl group and a glycidyl-based polymer, and particularly preferably a polyalkylene oxide having a hydrolyzable silyl group, a glycidyl-based polymer, and an acrylic polymer having a hydrolyzable silyl group. When the synthetic resin contains a polymer having a hydrolyzable silyl group and a glycidyl-based polymer, the combustion residue of the solid matter of the synthetic resin composition can be stably held. For example, the combustion residue of the solid matter of the synthetic resin composition can be stably held in a sealing part such as a joint part, and the fire resistance of the wall part of the building structure can be maintained. Furthermore, a decorative item such as a tile attached to a wall surface using the synthetic resin composition can be stably maintained in a state attached to the wall surface even in the event of a fire.

[0066] When the synthetic resin contains a polymer having a hydrolyzable silyl group and a glycidyl polymer, the content of the glycidyl polymer is preferably 1 to 100 parts by mass, more preferably 5 to 60 parts by mass, more preferably 7 to 50 parts by mass, and particularly preferably 8 to 40 parts by mass, relative to 100 parts by mass of the polymer having a hydrolyzable silyl group. When the content of the glycidyl polymer is 1 part by mass or more, the combustion residue of the solid matter of the synthetic resin composition can be stably maintained. When the content of the glycidyl polymer is 100 parts by mass or less, the solid matter of the synthetic resin composition can be preferably compatible with the flexibility of the polymer having a hydrolyzable silyl group and the toughness of the glycidyl polymer.

[0067] [mineral] The synthetic resin composition contains a mineral having a Mohs hardness of 5 or more. Examples of minerals having a Mohs hardness of 5 or more include feldspar, iron oxide, titanium oxide, silica (SiO 2 ), quartz, α-alumina, silicon carbide, boron carbide, etc. are preferred, with feldspar, titanium oxide, and α-alumina being more preferred, and feldspar being particularly preferred.

[0068] The Mohs hardness of a mineral is measured as follows. Ten standard minerals with different hardnesses [standard minerals with Mohs hardnesses between 1 and 10 (integer)] are prepared. The standard minerals with lower Mohs hardness are rubbed in order on the surface of the mineral to be measured. Among the standard minerals that did not scratch the surface of the mineral to be measured, the Mohs hardness of the standard mineral with the highest Mohs hardness is taken as the Mohs hardness of the mineral.

[0069] The feldspars include feldspar and feldspar spheroids, and feldspar spheroids are preferred. The feldspars may be used alone or in combination of two or more kinds.

[0070] Examples of feldspar include alkali feldspars such as orthoclase, sanidine, microcline, and anorthoclase; and plagioclases such as albite, oligoclase, andesine, albite, anorthite, and anorthite.

[0071] Examples of feldspar include nepheline such as kalsilite and cancrinite, nepheline syenite, leucite, sodalite, hauyne, lazurite, nosean, melilite, and the like, with nepheline syenite being preferred. Note that nepheline syenite is sometimes referred to as syenite.

[0072] The average particle size of the mineral is 0.01 to 100 μm, preferably 0.1 to 50 μm, more preferably 1 to 25 μm, particularly preferably 2 to 15 μm, and particularly preferably 3 to 10 μm. When the average particle size of the mineral is 0.01 μm or more, the combustion residue of the solid matter of the synthetic resin composition has excellent strength, which is preferable. When the average particle size of the mineral is 100 μm or less, the mineral can be uniformly dispersed in the synthetic resin composition, and the combustion residue of the solid matter of the synthetic resin composition has excellent strength.

[0073] The average particle size of the mineral refers to a value measured by image analysis using a transmission electron microscope. Specifically, a magnified photograph of the mineral is taken at 100 times magnification using a transmission electron microscope, 50 minerals are randomly selected, the diameter of each mineral is measured, and the arithmetic mean of the diameters of each mineral is taken as the average particle size of the mineral. The diameter of the mineral refers to the diameter of the smallest circle that can surround the mineral.

[0074] The content of the mineral in the synthetic resin composition is preferably 1 to 800 parts by mass, more preferably 30 to 600 parts by mass, more preferably 50 to 450 parts by mass, particularly preferably 80 to 300 parts by mass, and most preferably 120 to 200 parts by mass, relative to 100 parts by mass of the synthetic resin. When the content of the mineral is within the above range, the combustion residue of the solid matter of the synthetic resin composition has excellent strength, and the combustion residue does not become too hard and does not crack. Therefore, the state in which the sealing parts such as joints are filled can be reliably maintained, and the fire resistance of the wall of the architectural structure can be maintained. Furthermore, decorative items such as tiles attached to the wall surface using the synthetic resin composition can be stably maintained in the state of being attached to the wall surface even in the event of a fire.

[0075] [Binder components] The synthetic resin composition contains a binder component for binding minerals together in the combustion residue of the solid matter of the synthetic resin composition.

[0076] The binder component is not particularly limited, but glass frit (glass powder) and boric acid compounds are preferred, and glass frit is preferred. The binder components may be used alone or in combination of two or more.

[0077] [Glass frit] Examples of the glass constituting the glass frit include phosphate-based glass, borate-based glass, bismuth oxide-based glass, silicate-based glass, and sodium oxide-based glass. Phosphate-based glass and borate-based glass are preferred, and phosphate-based glass is more preferred. These glass frits are B 2 O 3 , P 2 O5 , ZnO, SiO 2 , Bi 2 O 3 , Al 2 O 3 , BaO, CaO, MgO, MnO 2 , ZrO 2 , TiO 2 , CEO 2 , SrO, V 2 O 5 , SnO 2 , Li 2 O, Na 2 OK 2 O, CuO, Fe 2 O 3 The glass frit may be used alone or in combination of two or more kinds.

[0078] The softening point of the glass constituting the glass frit is preferably 350 to 650° C., more preferably 360 to 560° C., particularly preferably 370 to 540° C., and most preferably 380 to 520° C. The softening point of the glass constituting the glass frit is the temperature at which the viscosity of the glass becomes 107.6 dPa s (log η = 7.6).

[0079] [Boric acid compounds] The boric acid compound is not particularly limited, and examples thereof include zinc borate, ammonium borate, sodium borate, potassium borate, calcium borate, and the like, with zinc borate being preferred.

[0080] The content of the binder component in the synthetic resin composition is preferably 2 to 120 parts by mass, more preferably 5 to 100 parts by mass, more preferably 8 to 90 parts by mass, particularly preferably 25 to 90 parts by mass, and most preferably 30 to 60 parts by mass, relative to 100 parts by mass of the synthetic resin. When the content of the binder component is within the above range, the combustion residue of the solid matter of the synthetic resin composition has excellent strength, and the combustion residue does not become too hard and does not crack. Therefore, the state in which the sealing parts such as joints are filled can be reliably maintained, and the fire resistance of the wall of the architectural structure can be maintained. Furthermore, decorative items such as tiles attached to the wall surface using the synthetic resin composition can be stably maintained in the state of being attached to the wall surface even in the event of a fire.

[0081] In the synthetic resin composition, the ratio of the mineral content to the binder content (mineral content / binder content) is preferably 1 to 20, more preferably 2 to 15, more preferably 2.5 to 12, particularly preferably 3 to 10, and most preferably 3.5 to 7. When the ratio of the mineral content to the binder content (mineral content / binder content) is within the above range, the combustion residue of the solid matter of the synthetic resin composition has excellent strength, and the combustion residue does not become too hard and does not crack. Therefore, the state of sealing parts such as joints being filled can be reliably maintained, and the fire resistance of the wall of the architectural structure can be maintained. Furthermore, decorative items such as tiles attached to the wall surface using the synthetic resin composition can be stably maintained in the state of being attached to the wall surface even in the event of a fire.

[0082] [Leaving agent] The synthetic resin composition may contain an expanding agent. The solid matter of the synthetic resin composition is filled in sealing parts such as joints formed in the walls of a building structure, but for example, the wall members constituting the walls shrink due to heat during a fire, and as a result, the joints formed between the wall members expand.

[0083] Therefore, it is preferable to include an expansion agent in the synthetic resin composition, since the solid matter of the synthetic resin composition can be expanded when the solid matter is burned. In particular, the solid matter of the synthetic resin composition can be smoothly adapted to the expansion of the sealing portion when the solid matter of the synthetic resin composition is burned, so that the sealing portion can be reliably kept closed.

[0084] The expanding agent is not particularly limited, but calcium carbonate (Mohs hardness: 3), a compound containing magnesium silicate (Mohs hardness: 1), expanded graphite (Mohs hardness: 1), aluminum hydroxide (Mohs hardness: 3) and magnesium hydroxide (Mohs hardness: 3) are preferred, and calcium carbonate and a compound containing magnesium silicate are more preferred, and a compound containing magnesium silicate is particularly preferred, since the strength of the combustion residue of the solid matter of the synthetic resin composition is increased. The expanding agent may be used alone or in combination of two or more kinds. The Mohs hardness of the expanding agent is preferably 3 or less. When the Mohs hardness of the expanding agent is 3 or less, the solid matter of the synthetic resin composition can be smoothly expanded when it is burned. The Mohs hardness of the expanding agent is measured in the same manner as when measuring the Mohs hardness of a mineral.

[0085] [Magnesium silicate-containing compounds] The compound containing magnesium silicate is not particularly limited, and examples thereof include natural compounds containing magnesium silicate, such as compounds containing magnesium silicate, such as sepiolite, attapulgite, talc, forsterite, humite, enstatite, clinoenstatite, and chrysotile, and magnesium calcium silicates, such as oromanite, magnesia axinite, diopsite, and tremolite. Sepiolite, attapulgite, and talc are more preferred in that they can improve the strength of the combustion residue, and sepiolite is more preferred.

[0086] [Calcium carbonate] The calcium carbonate is not particularly limited, and examples thereof include colloidal calcium carbonate, heavy calcium carbonate, light calcium carbonate, etc., with colloidal calcium carbonate and heavy calcium carbonate being preferred, and colloidal calcium carbonate being more preferred.

[0087] The average particle size of calcium carbonate is preferably 0.01 to 5 μm, more preferably 0.05 to 2.5 μm. With calcium carbonate having such an average particle size, the combustion residue of the solid matter of the synthetic resin composition has excellent strength, and the combustion residue does not become too hard and does not crack. Therefore, the filled state of sealing parts such as joints can be reliably maintained, and the fire resistance of the wall of the building structure can be maintained. The average particle size of calcium carbonate refers to a value measured by averaging 10 particles measured on a scale by SEM observation.

[0088] In addition, the calcium carbonate is preferably surface-treated with a fatty acid, a fatty acid ester, etc. Calcium carbonate surface-treated with a fatty acid, a fatty acid ester, etc. can impart thixotropy to the synthetic resin composition and can inhibit the calcium carbonate from aggregating.

[0089] [Expanded graphite] Expanded graphite is produced by treating natural or synthetic graphite with an intercalant such as an acid, oxidant, or halide to create an intercalation compound, and then rapidly heating the powder (1000 to 1200°C) to expand the graphite in the c-axis direction by approximately 150 to 700 times.

[0090] Intercalant materials include sulfuric acid, nitric acid, chromic acid, boric acid, and SO 3 , or FeCl 3 , ZnCl 2 , and SbCl 5 Examples of halides include:

[0091] The content of the expansion agent in the synthetic resin composition is preferably 1 to 100 parts by mass, more preferably 2 to 50 parts by mass, and particularly preferably 2 to 30 parts by mass, relative to 100 parts by mass of the synthetic resin. When the content of the expansion agent is within the above range, the solid matter of the synthetic resin composition can be expanded during combustion to smoothly follow size changes such as expansion of the sealing part, and the sealing part can be reliably maintained in a closed state. When a natural mineral containing magnesium silicate is used as the expansion agent, the magnesium silicate in the natural mineral may be adjusted to be within the above range.

[0092] In the synthetic resin composition, the ratio of the mineral content to the expansion agent content (mineral content / expansion agent content) is preferably 1 or more, more preferably 3 or more, more preferably 10 or more, and particularly preferably 20 or more, since it can improve the strength of the combustion residue of the synthetic resin composition and suppress the occurrence of cracks in the solid matter of the synthetic resin composition. In the synthetic resin composition, the ratio of the mineral content to the expansion agent content (mineral content / expansion agent content) is preferably 350 or less, more preferably 200 or less, more preferably 100 or less, more preferably 80 or less, and particularly preferably 60 or less, since it can effectively block the sealing part. When a natural mineral containing magnesium silicate is used as the expansion agent, the magnesium silicate in the natural mineral may be adjusted to be within the above range.

[0093] [Plasticizer] The synthetic resin composition preferably contains a plasticizer. Examples of the plasticizer include phthalates such as dimethyl phthalate, diethyl phthalate, dibutyl phthalate, diisobutyl phthalate, di-n-hexyl phthalate, bis(2-ethylhexyl) phthalate, di-n-octyl phthalate, diisononyl phthalate, dinonyl phthalate, diisodecyl phthalate, diisoundecyl phthalate, and bisbutylbenzyl phthalate; and polyalkylene glycols such as diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, tripropylene glycol, tetrapropylene glycol, and polypropylene glycol. Among these, polyalkylene glycols are preferred, and polypropylene glycol is more preferred. The plasticizer is a phthalate having a viscosity of 1.01×10 at 23° C. and 1.01×10 5 It is preferable that the material is in a liquid state at 1 atm.

[0094] When the plasticizer is a polymer, the number average molecular weight of the plasticizer is preferably 1000 to 10000, more preferably 2000 to 5000. When the number average molecular weight of the plasticizer is within the above range, the combustion residue of the solid matter of the synthetic resin composition is stably retained in sealing parts such as joints, and excellent fire resistance can be imparted to the walls of architectural structures.

[0095] In the present invention, when the plasticizer is a polymer, the number average molecular weight of the plasticizer is a value measured in terms of polystyrene by GPC (gel permeation chromatography). The specific measurement method and measurement conditions are the same as those for the polyalkylene oxide described above.

[0096] The content of the plasticizer in the synthetic resin composition is preferably from 1 to 50 parts by mass, and more preferably from 10 to 40 parts by mass, per 100 parts by mass of the synthetic resin.

[0097] [Dehydrating agent] The synthetic resin composition preferably further contains a dehydrating agent, which can prevent the synthetic resin composition from being hardened by moisture contained in the air or the like during storage.

[0098] Examples of the dehydrating agent include silane compounds such as vinyltrimethoxysilane, dimethyldimethoxysilane, tetraethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, tetramethoxysilane, phenyltrimethoxysilane, and diphenyldimethoxysilane; and ester compounds such as methyl orthoformate, ethyl orthoformate, methyl orthoacetate, and ethyl orthoacetate. These dehydrating agents may be used alone or in combination of two or more. Among them, vinyltrimethoxysilane is preferred.

[0099] The content of the dehydrating agent in the synthetic resin composition is preferably 0.5 to 20 parts by mass, more preferably 1 to 15 parts by mass, based on 100 parts by mass of the synthetic resin. When the content of the dehydrating agent in the synthetic resin composition is 0.5 parts by mass or more, the effect obtained by the dehydrating agent is sufficiently obtained. Also, when the content of the dehydrating agent in the synthetic resin composition is 20 parts by mass or less, the synthetic resin composition has excellent curability.

[0100] [Silanol condensation catalyst] The synthetic resin composition preferably contains a silanol condensation catalyst. The silanol condensation catalyst is a catalyst for promoting a dehydration condensation reaction between silanol groups formed by hydrolysis of hydrolyzable silyl groups and the like contained in the synthetic resin.

[0101] Examples of the silanol condensation catalyst include organic tin compounds such as 1,1,3,3-tetrabutyl-1,3-dilauryloxycarbonyl-distannoxane, dibutyltin dilaurate, dibutyltin oxide, dibutyltin diacetate, dibutyltin phthalate, bis(dibutyltin laurate) oxide, dibutyltin bis(acetylacetonate), dibutyltin bis(monoester maleate), tin octoate, dibutyltin octoate, dioctyltin oxide, dibutyltin bis(triethoxysilicate), bis(dibutyltin bistriethoxysilicate) oxide, and dibutyltin oxybisethoxysilicate; organic titanium compounds such as tetra-n-butoxy titanate and tetraisopropoxy titanate. These silanol condensation catalysts may be used alone or in combination of two or more.

[0102] The silanol condensation catalyst is preferably 1,1,3,3-tetrabutyl-1,3-dilauryloxycarbonyl-distannoxane, which makes it possible to easily adjust the curing speed of the synthetic resin composition.

[0103] The content of the silanol condensation catalyst in the synthetic resin composition is preferably 1 to 10 parts by mass, more preferably 1 to 5 parts by mass, relative to 100 parts by mass of the synthetic resin. When the content of the silanol condensation catalyst in the synthetic resin composition is 1 part by mass or more, the curing speed of the synthetic resin composition can be increased, and the time required for curing the synthetic resin composition can be shortened. When the content of the silanol condensation catalyst in the synthetic resin composition is 10 parts by mass or less, the synthetic resin composition has an appropriate curing speed, and the storage stability and handling of the synthetic resin composition can be improved.

[0104] [Other additives] The synthetic resin composition may contain other additives such as a thixotropic agent, an antioxidant, an ultraviolet absorber, a pigment, a dye, an antisettling agent, an aminosilane coupling agent, a thixotropic agent, and a solvent. Among these, the thixotropic agent, the ultraviolet absorber, and the antioxidant are preferred.

[0105] The thixotropic agent may be any agent capable of imparting thixotropy to the synthetic resin composition. Preferred examples of the thixotropic agent include hydrogenated castor oil, fatty acid bisamide, and fumed silica.

[0106] The content of the thixotropy-imparting agent in the synthetic resin composition is preferably 0.1 to 200 parts by mass, more preferably 1 to 150 parts by mass, relative to 100 parts by mass of the synthetic resin. When the content of the thixotropy-imparting agent in the synthetic resin composition is 0.1 parts by mass or more, thixotropy can be effectively imparted to the synthetic resin composition. When the content of the thixotropy-imparting agent in the synthetic resin composition is 200 parts by mass or less, the synthetic resin composition has an appropriate viscosity, and the handleability of the synthetic resin composition is improved.

[0107] Examples of the ultraviolet absorbent include benzotriazole-based ultraviolet absorbents and benzophenone-based ultraviolet absorbents, and benzotriazole-based ultraviolet absorbents are preferred. The content of the ultraviolet absorbent in the synthetic resin composition is preferably 0.1 to 20 parts by mass, more preferably 0.1 to 10 parts by mass, based on 100 parts by mass of the synthetic resin.

[0108] Examples of the antioxidant include hindered phenol-based antioxidants, monophenol-based antioxidants, bisphenol-based antioxidants, and polyphenol-based antioxidants, and the like, with the hindered phenol-based antioxidants being preferred. The content of the antioxidant in the synthetic resin composition is preferably 0.1 to 20 parts by mass, more preferably 0.3 to 10 parts by mass, relative to 100 parts by mass of the synthetic resin.

[0109] [Light stabilizer] The synthetic resin composition preferably contains a hindered amine-based light stabilizer. The hindered amine-based light stabilizer can provide a synthetic resin composition that can maintain excellent rubber elasticity for a long period of time after curing.

[0110] Examples of the hindered amine light stabilizer include a mixture of bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate and methyl 1,2,2,6,6-pentamethyl-4-piperidylsebacate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, dibutylamine·1,3,5-triazine·N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl-1,6-hexamethylenediamine and N-(2,2,6,6 poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino}], and a polycondensate of dimethyl succinate and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidineethanol.

[0111] As the hindered amine-based light stabilizer, a NOR-type hindered amine-based light stabilizer is preferably used. The NOR-type hindered amine-based light stabilizer can provide a synthetic resin composition in which the decrease in rubber elasticity over time after curing is suppressed.

[0112] The NOR type hindered amine light stabilizer has a NOR structure in which an alkyl group (R) is bonded to a nitrogen atom (N) contained in a piperidine ring skeleton via an oxygen atom (O). The number of carbon atoms in the alkyl group in the NOR structure is preferably 1 to 20, more preferably 1 to 18, and particularly preferably 18. Examples of the alkyl group include a linear alkyl group, a branched alkyl group, and a cyclic alkyl group (a saturated alicyclic hydrocarbon group).

[0113] Examples of linear alkyl groups include methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-octyl, n-nonyl, and n-decyl groups. Examples of branched alkyl groups include isopropyl, isobutyl, sec-butyl, and tert-butyl. Examples of cyclic alkyl groups (saturated alicyclic hydrocarbon groups) include cyclopentyl, cyclohexyl, and cyclooctyl groups. In addition, the hydrogen atoms constituting the alkyl groups may be substituted with halogen atoms (e.g., fluorine, chlorine, and bromine atoms) or hydroxyl groups.

[0114] The NOR type hindered amine light stabilizer includes a hindered amine light stabilizer represented by the following formula (I).

[0115] [ka]

[0116] When a NOR type hindered amine light stabilizer is used, it is preferable to use the NOR type hindered amine light stabilizer in combination with a benzotriazole type ultraviolet absorber or a triazine type ultraviolet absorber, which can provide a synthetic resin composition in which the decrease in rubber elasticity over time after curing is more significantly suppressed.

[0117] The content of the hindered amine light stabilizer in the synthetic resin composition is preferably from 0.01 to 20 parts by mass, and more preferably from 0.1 to 10 parts by mass, based on 100 parts by mass of the synthetic resin.

[0118] The synthetic resin composition can be produced by mixing a synthetic resin, a mineral, a binder component, and additives added as necessary. The synthetic resin composition may be in the form of a suspension or emulsion by being suspended or emulsified in an aqueous solvent. The synthetic resin composition may be in the form of a solution by being dissolved in a solvent. Examples of the aqueous solvent include alcohols such as ethyl alcohol, methyl alcohol, and isopropyl alcohol, and water. Examples of the solvent include xylene, toluene, and acetone.

[0119] The synthetic resin composition can be suitably used as a fireproof material, a sealing material, and an adhesive.

[0120] A joint structure can be constructed by using the synthetic resin composition as a sealant. As a method for applying the synthetic resin composition to a joint to obtain a joint structure, a method is used in which the synthetic resin composition is filled into the joint and then cured to harden or cool and solidify. The obtained joint structure includes a wall member constituting the wall of an architectural structure, and a solid of the synthetic resin composition filled into a joint formed between adjacent wall members. Examples of the wall of an architectural structure include an exterior wall, an interior wall, and a ceiling. Examples of the wall member include an exterior wall member, an interior wall member, and a ceiling member.

[0121] The joints are not particularly limited, and examples thereof include joints in the outer walls, inner walls, and ceilings of architectural structures. The synthetic resin composition can maintain excellent rubber elasticity for a long period of time after curing, and therefore exhibits excellent followability to changes in the width of the joints due to expansion and contraction of members caused by temperature changes such as air temperature and sunlight, or due to the action of vibration and wind pressure, and can prevent damage to members and water leakage into architectural structures. Therefore, it is suitable for use in sealing joints with large changes in width, also known as "working joints," such as joints in the outer walls of architectural structures.

[0122] Examples of joints in the exterior walls of architectural structures include joints that occur at the junctions between exterior wall members such as mortar boards, concrete boards, ceramic siding boards, metal siding boards, ALC boards, and metal plates.

[0123] Furthermore, the solid matter of the synthetic resin composition produces strong combustion residues upon combustion, and these combustion residues fill and reliably keep the joints of the building structure sealed even in the event of a fire, preventing flames from penetrating through the joints and imparting excellent fire resistance to the walls of the building structure.

[0124] Furthermore, when the synthetic resin composition contains an expanding agent, the solid matter of the synthetic resin composition expands during combustion to generate combustion residues. Therefore, even if the sealing part, such as a joint part, filled with the synthetic resin composition expands, the synthetic resin composition smoothly follows the expansion of the sealing part, stably maintaining the filling and blocking state of the sealing part, and can impart excellent fire resistance to the wall part of the building structure.

[0125] Another example of the usage of the synthetic resin composition will be described. Specifically, the synthetic resin composition can be suitably used as an adhesive. The usage of the synthetic resin composition will be described by taking as an example the usage of the synthetic resin composition to attach and integrate tiles, which are decorative items, onto the surface of a wall.

[0126] The synthetic resin composition is molten. Next, the molten synthetic resin composition is applied to the back surface of a tile, and the tile is attached to a predetermined location on the wall surface via the synthetic resin composition. The synthetic resin composition is then cooled and solidified or cured, and the tile is attached and integrated to the predetermined location on the wall surface via the synthetic resin composition. Examples of the wall of an architectural structure include an exterior wall, an interior wall, and a ceiling.

[0127] The hardened synthetic resin composition produces strong combustion residues upon combustion, and these combustion residues firmly hold decorative items such as tiles that are attached and integrated onto the wall surface of an architectural structure even in the event of a fire, preventing the decorative items from falling off the wall surface in the event of a fire.

[0128] A fire-resistant material can be formed using the synthetic resin composition. By incorporating the synthetic resin composition into a molded product formed from an organic or inorganic material, the molded product can be made into a fire-resistant material. Even if the molded product is burned and becomes a combustion residue, it can retain its shape and prevent the combustion residue from collapsing. The molded product is not particularly limited, and examples thereof include wallpaper, decorative sheets, substrates (e.g., wall panels, floor panels, etc.), and building materials such as paper. Effect of the Invention

[0129] The synthetic resin composition of the present invention produces extremely strong combustion residues upon combustion, which reliably fill and seal joints even in the event of a fire, preventing flames from penetrating through sealing parts such as joints, thereby imparting excellent fire resistance to the walls of building structures and the like.

[0130] The synthetic resin composition of the present invention produces a very strong combustion residue upon combustion, which can reliably hold decorative items such as tiles attached to a wall surface even in the event of a fire, effectively preventing the decorative items from falling off the wall. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0131] The present invention will be described in more detail below using examples, but the present invention is not limited thereto. EXAMPLES

[0132] The following raw materials were used in producing the synthetic resin compositions of the Examples and Comparative Examples.

[0133] [Synthetic resin] Polyalkylene oxide 1 having a hydrolyzable silyl group (polyalkylene oxide whose main chain skeleton is made of polypropylene oxide and has a propyldimethoxysilyl group at the end of the main chain, average number of propyldimethoxysilyl groups per molecule: 2.1, number average molecular weight: 20,000, manufactured by Kaneka Corporation, product name "MS Polymer S-303") Polyalkylene oxide 2 having a hydrolyzable silyl group (polyalkylene oxide whose main chain skeleton is made of polypropylene oxide and has a methyldimethoxysilyl group at the end of the main chain, average number of propyldimethoxysilyl groups per molecule: 2.1, number average molecular weight: 15,000, manufactured by Kaneka Corporation, product name "Kaneka Silyl EST280") Acrylic resin with hydrolyzable silyl group (acrylic resin whose main chain structure is made of methyl methacrylate-butyl acrylate copolymer and has trimethoxysilyl group in part of the main chain, average number of trimethoxysilyl groups per molecule: 0.3, weight average molecular weight: 4000, manufactured by Toagosei Co., Ltd., product name "US-6150") Silicone resin with hydrolyzable silyl groups (silicone resin with ketoximesilyl groups, manufactured by Sekisui Fuller Co., Ltd., product name "Sekisui Silicone Sealant") Glycidyl polymer 1 (a two-part curable resin consisting of a base agent containing epoxy resin (manufactured by Sekisui Fuller Co., Ltd., product name "Joiner WA Agent") and a curing agent containing polyoxypropylene triamine (manufactured by Sekisui Fuller Co., Ltd., product name "Joiner WB Agent") Glycidyl polymer 2 (a two-part curable resin consisting of a base material containing epoxy resin (Toa Gosei Co., Ltd.'s product name "JER828") and an amine-based curing agent containing 2,4,6-tris(dimethylaminomethyl)phenol) Glycidyl polymer 3 (a two-liquid curable resin consisting of a base agent containing an epoxy resin (manufactured by Toa Gosei Co., Ltd., product name "JER828") and a curing agent containing a ketimine compound (manufactured by Nitto Kasei Co., Ltd., product name "Eponit K-100")) - A two-part curable resin consisting of a base agent containing an isocyanate polymer (diphenylmethane diisocyanate (manufactured by Sekisui Fuller Co., Ltd., product name "#558") and a curing agent containing a castor oil-based polyol (manufactured by Sekisui Fuller Co., Ltd., product name "UX-B") Urethane resin 1 having hydrolyzable isocyanate groups (polyester polyurethane resin, manufactured by Sekisui Fuller Co., Ltd., product name "#9611B") - Urethane resin 2 having hydrolyzable isocyanate groups (polyether-based urethane resin having isocyanate groups, manufactured by Sekisui Fuller Co., Ltd., product name "#500G") Polyolefin resin (hot melt adhesive, Sekisui Fuller product name "JM-1733") Emulsion polymer (a water-based adhesive mainly composed of vinyl acetate as a monomer unit (manufactured by Sekisui Fuller Co., Ltd., product name "Esdyne #5406", solid content: 45% by mass)

[0134] [mineral] Feldspar (Mohs hardness: 6, average particle size: 5 μm, nepheline syenite, manufactured by Shiraishi Calcium Co., Ltd., product name "Nespar") Titanium oxide (Mohs hardness: 7, average particle size: 0.3 μm, Ishihara Sangyo Kaisha, Ltd. product name "CR-90") α-alumina (Mohs hardness: 9, average particle size: 0.5 μm, manufactured by Wako Pure Chemical Industries, Ltd., product name "α-alumina")

[0135] [Binder components] Glass frit (phosphate glass, Nippon Frit Co., Ltd. "VY0144", main component: P 2 O 5 , AI 2 O 3 and R 2 O and R are alkali metal atoms, softening point: 404℃) Zinc borate (manufactured by Rio Tinto Minerals Asia Pte Ltd, product name "Fire brake 500")

[0136] [Leaving agent] Colloidal calcium carbonate (Shiraishi Kogyo Co., Ltd., product name "CCR", average particle size: 80 nm, Mohs hardness: 3) Magnesium silicate hydrate (sepiolite, Showa KDE product name "Milcon E-2", average particle size: 1 μm, magnesium silicate: 97% by mass, Mohs hardness: 1) Magnesium silicate and aluminum silicate (atapulgite, Sun Ocean product name "Atagel #50", average particle size: 0.1 μm, magnesium silicate: 97% by mass, Mohs hardness: 1) Expanded graphite (manufactured by Air Water Corporation, product name "TEG", Mohs hardness: 1) Aluminum hydroxide (manufactured by NabaiTec, product name "APYRAL AG", Mohs hardness: 3) Magnesium hydroxide (manufactured by Konoshima Chemical Co., Ltd., product name "Magseeds N-6", Mohs hardness: 3)

[0137] [Other additives] Silanol condensation catalyst (1,1,3,3-tetrabutyl-1,3-dilauryloxycarbonyl-distannoxane, manufactured by Nitto Kasei Co., Ltd., product name "Neostan U-130") Dehydrating agent (vinyltrimethoxysilane, manufactured by Nippon Unika Co., Ltd., product name "NUC Silicone A171") Aminosilane coupling agent (N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, Shin-Etsu Chemical Co., Ltd., product name KBM-603) Epoxy silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., product name "KBM-403") Benzotriazole-based UV absorber (BASF Japan product name: Tinuvin 326) Hindered phenol antioxidant (BASF Japan product name "Irganox 1010") NH-type hindered amine light stabilizer (BASF Japan product name: Tinuvin 770) · Thixotropic agent (fatty acid amide wax, product name "Disparlon #6500" manufactured by Kusumoto Chemicals Co., Ltd.) Fatty amines (stearylamine) Plasticizer (polypropylene glycol, number average molecular weight: 3000) · Solvent (isopropyl alcohol)

[0138] (Examples 1 to 38, Comparative Examples 1 to 10) The synthetic resin, mineral, binder component, expansion agent and other additives were mixed in the amounts shown in Tables 1 to 6 using a planetary mixer under a vacuum atmosphere for 60 minutes until the mixture was uniform, to obtain a synthetic resin composition. When the synthetic resin was a two-component curable resin, the base resin, mineral, binder component, expansion agent and additives were mixed to form the first component, and the curing agent was used as the second component. The synthetic resin composition was a two-component type consisting of the first and second components. The first and second components of the synthetic resin composition were mixed immediately before use, and the two-component curable resin was cured. For the emulsion polymer, the mass of the solid content was recorded.

[0139] The synthetic resin compositions were burned in an atmosphere at 800° C. for 20 minutes, and the strength of the combustion residues was measured in the manner described above. The results are shown in Tables 1-6.

[0140] For the synthetic resin compositions of Examples 1 to 21, 25, and 27, and Comparative Examples 1 to 4, the 50% modulus and elongation percentage after aging for 28 days at 23°C and 50% relative humidity were measured in the manner described above for I-type test specimens in accordance with the NPO Housing Exterior Wall Technical Center standard JTC S-0001. The results are shown in Tables 1, 2, 4, and 6.

[0141] The synthetic resin compositions of Examples 1 to 26 and Comparative Examples 1 to 4 were burned in an atmosphere of 800° C. for 20 minutes, and the joint conformability of the combustion residue was measured as described below. The results are shown in Tables 1 to 4 and 6.

[0142] The shear strength of the synthetic resin compositions of Examples 22 to 24, 27 to 38 and Comparative Examples 5 to 10 was measured in the manner described above. The results are shown in Tables 3, 5 and 6.

[0143] For the synthetic resin compositions of Examples 22 to 24, 27 to 38 and Comparative Examples 5 to 10, the tile retention was measured in the following manner. The results are shown in Tables 3, 5 and 6.

[0144] (Joint-following ability of combustion residue) Two sheets of exterior wall material (manufactured by Asahi Kasei Corporation, product name "ALC") were prepared. The two sheets of exterior wall material were arranged so that the distance between the opposing surfaces of these exterior wall materials was 10 mm. A sealing part was formed by the gap between the exterior wall materials. This sealing part was filled with a synthetic resin composition, and cured at 23°C and a relative humidity of 50% for 28 days to form a test specimen. The test specimen was burned for 20 minutes in an atmosphere of 800°C. The size of the gap between the exterior wall material and the combustion residue of the synthetic resin composition was measured using a gap gauge. Evaluation was made according to the following criteria based on the size of the gap. A (less than 0.5 mm) B (0.5 mm or more and less than 1.0 mm) C (1.0mm or more)

[0145] (Tile retention) Four tiles were prepared, each of which had a square shape with a side of 15 cm and a flat surface. The synthetic resin composition was melted and then applied at 100 g / m2 to the entire back surface of each tile. 2 The coating amount was 100%.

[0146] Next, a mortar exterior wall material was prepared, and four tiles were placed on the surface of this exterior wall material with the synthetic resin composition facing the exterior wall material, and the synthetic resin composition was then cooled and solidified or hardened to attach and integrate the tiles onto the surface of the exterior wall material to prepare a test specimen. The interval between adjacent tiles was 0.5 cm.

[0147] When the synthetic resin composition was cooled and solidified, the synthetic resin composition was left for 60 minutes in an environment at 23° C. When the synthetic resin composition was cured, the synthetic resin composition was aged for one month in an environment at 23° C. and a relative humidity of 50%.

[0148] The obtained test specimen was left in a constant temperature bath at 600°C for 30 minutes to be burned, then the test specimen was removed from the constant temperature bath and left in an atmosphere at 23°C for 3 hours. Then, with the exterior wall material standing vertically, the presence or absence of falling off of the four tiles was observed. A (The four tiles did not fall off and were very firmly attached.) B (Four tiles had not fallen off, but they were in a state where they could be easily removed by touching with the hand.) C (One to three tiles had fallen off.) D (All four tiles had fallen off.)

[0149] [Table 1]

[0150] [Table 2]

[0151] [Table 3]

[0152] [Table 4]

[0153] [Table 5]

[0154] [Table 6] [Industrial Applicability]

[0155] The synthetic resin composition of the present invention has a very strong combustion residue generated by combustion. The synthetic resin composition can be suitably used as a sealant. The combustion residue fills and reliably keeps the joints sealed even in the event of a fire, preventing flames from penetrating through the sealing parts such as the joints, and can impart excellent fire resistance to the walls of architectural structures.

[0156] The synthetic resin composition can also be suitably used as an adhesive. The combustion residue can, for example, reliably hold decorative items such as tiles attached to the wall surface even in the event of a fire, and can effectively prevent the decorative items from falling off the wall.

[0157] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims priority to Japanese Patent Application No. 2018-089675, filed May 8, 2018, and Japanese Patent Application No. 2018-089677, filed May 8, 2018, the disclosures of which are incorporated herein by reference in their entirety.

Claims

1. It contains synthetic resin, and the strength of the combustion residue after burning for 20 minutes in an atmosphere of 800°C is 0.5 N / mm 2 The synthetic resin composition as described above. The strength of the combustion residue is a film strength of the combustion residue measured by: applying the synthetic resin composition in a molten state onto a zinc ore plate to a thickness of 10 mm, width of 10 mm and length of 50 mm; curing the synthetic resin composition for one month in an environment of 23° C. and relative humidity of 50%; curing or solidifying the synthetic resin composition to obtain a test specimen; leaving the specimen in a thermostatic chamber at 800° C. for 20 minutes to burn it; removing the specimen from the thermostatic chamber; and leaving the specimen in an atmosphere of 23° C. and relative humidity of 50% for 3 hours to generate a combustion residue, the combustion residue being compressed at a compression speed of 50 mm / min using a universal testing machine with a needle having a diameter of 1.5 mm. The synthetic resin composition, wherein the synthetic resin is a curable resin, and the curable resin contains a polymer having a hydrolyzable silyl group.

2. A synthetic resin composition containing a synthetic resin, the strength of the combustion residue after burning for 20 minutes in an atmosphere of 800°C being 0.5 N / mm2 or more. The strength of the combustion residue is a film strength of the combustion residue measured by: applying the synthetic resin composition in a molten state onto a zinc ore plate to a thickness of 10 mm, width of 10 mm and length of 50 mm; curing the synthetic resin composition for one month in an environment of 23° C. and relative humidity of 50%; curing or solidifying the synthetic resin composition to obtain a test specimen; leaving the specimen in a thermostatic chamber at 800° C. for 20 minutes to burn it; removing the specimen from the thermostatic chamber; and leaving the specimen in an atmosphere of 23° C. and relative humidity of 50% for 3 hours to generate a combustion residue, the combustion residue being compressed at a compression speed of 50 mm / min using a universal testing machine with a needle having a diameter of 1.5 mm. The present invention comprises the synthetic resin, a mineral having a Mohs hardness of 5 or more, and a binder component that bonds the minerals together in the combustion residue, A synthetic resin composition, characterized in that the binder component contains at least one compound selected from the group consisting of glass frit and boric acid compounds.

3. 3. The synthetic resin composition according to claim 2, wherein the mineral having a Mohs hardness of 5 or more is a feldspar.

4. 4. The synthetic resin composition according to claim 3, wherein the feldspars include nepheline syenite.

5. 4. The synthetic resin composition according to claim 1, further comprising an expanding agent.

6. 6. The synthetic resin composition according to claim 5, wherein the expansion agent comprises calcium carbonate and / or magnesium silicate.

7. The 50% modulus of the I-type test specimen, which conforms to the standard JTC S-0001 of the NPO Housing Exterior Wall Technical Center, after curing for 28 days at 23°C and 50% relative humidity is 0.05 to 0.40 N / mm 2 7. The synthetic resin composition according to claim 1, wherein the elongation is 400% or more.

8. A synthetic resin composition containing a synthetic resin, the strength of the combustion residue after burning for 20 minutes in an atmosphere of 800°C being 0.5 N / mm2 or more. The strength of the combustion residue is measured by applying the synthetic resin composition in a molten state to a zinc ore plate to a thickness of 10 mm, a width of 10 mm, and a length of 50 mm, curing the synthetic resin composition for one month in an environment of 23° C. and a relative humidity of 50%, and curing or solidifying the synthetic resin composition to obtain a test specimen, which is left in a constant temperature bath at 800° C. for 20 minutes to be combusted, and then removed from the constant temperature bath and left in an atmosphere of 23° C. and a relative humidity of 50% for 3 hours to generate a combustion residue, which is a coating strength of the combustion residue measured by compressing the combustion residue at a compression speed of 50 mm / min with a needle having a diameter of 1.5 mm using a universal testing machine. A fire-resistant material characterized by containing a synthetic resin composition.

9. A synthetic resin composition containing a synthetic resin, the strength of the combustion residue after burning for 20 minutes in an atmosphere of 800°C being 0.5 N / mm2 or more. The strength of the combustion residue is measured by applying the synthetic resin composition in a molten state to a zinc ore plate to a thickness of 10 mm, a width of 10 mm, and a length of 50 mm, curing the synthetic resin composition for one month in an environment of 23°C and a relative humidity of 50%, and curing or solidifying the synthetic resin composition to obtain a test specimen, which is left in a constant temperature bath at 800°C for 20 minutes to be combusted, and then removed from the constant temperature bath and left in an atmosphere of 23°C and a relative humidity of 50% for 3 hours to generate a combustion residue, which is a film strength of the combustion residue measured by compressing it at a compression speed of 50 mm / min with a needle having a diameter of 1.5 mm using a universal testing machine.

10. A synthetic resin composition containing a synthetic resin, the strength of the combustion residue after burning for 20 minutes in an atmosphere of 800°C being 0.5 N / mm2 or more. The strength of the combustion residue is measured by: applying the synthetic resin composition in a molten state onto a zinc ore plate to a thickness of 10 mm, width of 10 mm and length of 50 mm; curing the synthetic resin composition for one month in an environment of 23°C and relative humidity of 50%; curing or solidifying the synthetic resin composition to obtain a test specimen; leaving the test specimen in a constant temperature bath at 800°C for 20 minutes to cause combustion; removing the test specimen from the constant temperature bath; and leaving the test specimen in an atmosphere of 23°C and relative humidity of 50% for 3 hours to generate a combustion residue; compressing the generated combustion residue with a needle having a diameter of 1.5 mm at a compression speed of 50 mm / min using a universal testing machine; and measuring the film strength of the combustion residue.

11. Shear strength measured in accordance with JIS K6850 is 1.0 N / mm 2 The adhesive according to claim 10, characterized in that

12. A wall member constituting a wall portion of an architectural structure; A joint structure comprising the sealant or a hardened product thereof according to claim 9 filled in a joint formed between the wall members.

Citation Information

Patent Citations

  • Resin composition for artificial marble

    JP1992265261A

  • Composition for adhesion of ceramic material and adhering method

    JP1998324577A

  • Hydrophobicity imparting particle

    JP2001226591A

  • Outer wall structural material

    JP2007162213A

  • Sealing method of automobile panel using body sealer for automobile

    JP2010215742A